A colossal-sized pyometra drainage in postmenopausal female - Bhati, Indra; Chandel, Manvika; Kudri, Balakrishna S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Pyometra is an infrequent gynecological emergency observed mostly in postmenopausal females. It requires prompt diagnosis and interventions, as it might be indicative of various gynecological malignancies and in rare cases it can also result in burst abdomen if left unaddressed. Hereby, is a case report of an 83-year-old debilitated female, P11L6, who presented with a large pyometra corresponding to 32 weeks size uterus. After she underwent a panel of radiological imaging and other investigations and ruling out all possibilities of malignancy, a decision to drain the pyometra under ultrasonography (USG) guidance was taken. The drainage required meticulous negotiation of the severely stenosed cervix. Finally, 2.5 liters of purulent fluid was drained out at once. Women was discharged in a healthy condition and advised for follow up.